2009
DOI: 10.1074/jbc.m109.005421
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Histone H3 Thr-45 Is Linked to Apoptosis

Abstract: Numerous post-translational modifications have been identified in histones. Most of these occur within the histone tails, but a few have been identified within the histone core sequences. Histone core post-translational modifications have the potential to directly modulate nucleosome structure and consequently DNA accessibility. Here, we identify threonine 45 of histone H3 (H3T45) as a site of phosphorylation in vivo. We find that phosphorylation of H3T45 (H3T45ph) increases dramatically in apoptotic cells, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 29 publications
(30 reference statements)
1
84
0
1
Order By: Relevance
“…Significance was estimated as in (B). While phosphorylation of the ShaDock may involve several kinases, including PKCd [35] or MSK1 [13], we showed that DYRK1A, mostly studied for its role in DS, positively regulates a number of immune gene promoters subject to HP1-mediated transcriptional repression. In fact, we found that DYRK1A positively regulates a very large number of inducible genes at which it may be required for maintenance of basal-level transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Significance was estimated as in (B). While phosphorylation of the ShaDock may involve several kinases, including PKCd [35] or MSK1 [13], we showed that DYRK1A, mostly studied for its role in DS, positively regulates a number of immune gene promoters subject to HP1-mediated transcriptional repression. In fact, we found that DYRK1A positively regulates a very large number of inducible genes at which it may be required for maintenance of basal-level transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Snail1 also upregulates the binding of P-Thr45 histone H3 to the CDH1 promoter. The role of this phosphorylation has not been investigated yet; in mammalian cells the only report associates it with apoptosis (Hurd et al, 2009). It is possible that the modification is not linked to apoptosis per se but it is the consequence of the …”
Section: Akt2 Interacts With Snail1mentioning
confidence: 99%
“…Finally, there are some lesser known C-terminal phosphorylations of H3 that appear to play roles in cellular physiology. H3 Thr45 is phosphorylated by protein kinase C, and this modification is involved in apoptosis of cells in which DNA is nicked (57). Thr45 has also been reported to be phosphorylated in budding yeast by the kinase Cdc7-Dbf4.…”
Section: Histone H3mentioning
confidence: 99%